The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9091951
|View full text |Cite
|
Sign up to set email alerts
|

Application of Integrated Optical Electric-Field Sensor on the Measurements of Transient Voltages in AC High-Voltage Power Grids

Abstract: Transient voltages in the power grid are the key for the fault analysis of a power grid, optimized insulation design, and the standardization of the high-voltage testing method. The traditional measuring equipment, based on electrical engineering, normally has a limited bandwidth and response speed, which are also featured by a huge size and heavy weight. In this paper, an integrated optical electric-field sensor based on the Pockels effect was developed and applied to measure the transient voltages on the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The proposed setup uses an optical power measurement scheme, i.e., as opposed to measurement of wavelength, and thus would be relatively cheaper when compared to the utilization of complex optical spectrum analyzers for the target application. Moreover, two additional research papers presented by Xie et al [4] and Xue et al [5] have also been categorized under the rubric "fiber optic sensing". For instance, Xie et al [4] reported the application of an integrated optical electric-field sensor on the measurements of transient voltages in AC high-voltage power grids.…”
Section: Fiber Optical Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed setup uses an optical power measurement scheme, i.e., as opposed to measurement of wavelength, and thus would be relatively cheaper when compared to the utilization of complex optical spectrum analyzers for the target application. Moreover, two additional research papers presented by Xie et al [4] and Xue et al [5] have also been categorized under the rubric "fiber optic sensing". For instance, Xie et al [4] reported the application of an integrated optical electric-field sensor on the measurements of transient voltages in AC high-voltage power grids.…”
Section: Fiber Optical Sensingmentioning
confidence: 99%
“…Moreover, two additional research papers presented by Xie et al [4] and Xue et al [5] have also been categorized under the rubric "fiber optic sensing". For instance, Xie et al [4] reported the application of an integrated optical electric-field sensor on the measurements of transient voltages in AC high-voltage power grids. They developed an integrated optical electric-field sensor based on the Pockels effect to measure the transient voltages of high-voltage conductors and achieved a response speed faster than 6 ns and a wide bandwidth ranging from 5 Hz to 100 MHz [4].…”
Section: Fiber Optical Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 23 ], a system used for recording transients on a 220 kV and 500 kV power line is described. A specially developed optical sensor with a bandwidth of 5 Hz to 100 MHz was used as the sensor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their small size, these sensors do not have the problems of conventional measuring transformers such as waveform distortion and limited bandwidth. In [35], an example of these sensors designed to measure transient voltage signals is introduced, which has a bandwidth between 5 Hz and 100 MHz.…”
Section: Introductionmentioning
confidence: 99%